Slingshot homolog-1 mediates the secretion of small extracellular vesicles containing misfolded proteins by regulating autophagy cargo receptors and actin dynamics - Cazzaro, Sara; Fang, Cenxiao; Khan, Hirah; Witas, Richard; Kee, Teresa R.; Woo, Jung-A. A.; Kang, David E. (Frontiers in Aging Neuroscience, 2022)
Increasing evidence indicates that the accumulation misfolded proteins in Alzheimer’s disease (AD) arises from clearance defects in the autophagy-lysosome pathway. Misfolded proteins such as Aβ and tau are secreted in small extracellular vesicles (i.e., exosomes) and are propagated from cell to cell in part through secreted small extracellular vesicles (sEVs). Recent studies suggest that autophagic activity and exosome secretion are coregulated events, and multiple autophagy-related proteins are found in sEVs, including the cargo receptors Sqstm1/p62 and optineurin. However, whether and how autophagy cargo receptors per se regulate the secretion of sEVs is unknown. Moreover, despite the prominent role of actin dynamics in secretory vesicle release, its role in EV secretion is unknown. In this study, we leveraged the dual axes of Slingshot Homolog-1 (SSH1), which inhibits Sqstm1/p62-mediated autophagy and activates cofilin-mediated actin dynamics, to study the regulation of sEV secretion. Here we show that cargo receptors Sqstm1/p62 and optineurin inhibit sEV secretion, an activity that requires their ability to bind ubiquitinated cargo. Conversely, SSH1 increases sEV secretion by dephosphorylating Sqstm1/p62 at pSer403, the phospho-residue that allows Sqstm1/p62 to bind ubiquitinated cargo. In addition, increasing actin dynamics through the SSH1-cofilin activation pathway also increases sEV secretion, which is mimicked by latrunculin B treatment. Finally, Aβ42 oligomers and mutant tau increase sEV secretion and are physically associated with secreted sEVs. These findings suggest that increasing cargo receptor engagement with autophagic cargo and reducing actin dynamics (i.e. SSH1 inhibition) represents an attractive strategy to promote misfolded protein degradation while reducing sEV-mediated cell to cell spread of pathology.